Adaptation of in vitro cytoadherence assay to Plasmodium knowlesi field isolates - Farrah, A Fatih; Siner, Angela; Atique M, Ahmed; Lu, Chan Woon; Craig, Alister G; Staines, Henry M; Balbir, Singh; Sanjeev, Krishna; Cox-Singh, J. (BioMed Central Ltd., 2010)
P. knowlesi was the first Plasmodium species in which antigenic variation was observed. Variation was due to schizont infected cell agglutination (SICAvar) antigens expressed by the parasite and transported to the exposed surface of the host erythrocyte [1]. PfEMP1 is P. falciparum’s orthologue of P. knowlesi’s SICA proteins [2]. In P. falciparum PfEMP1 is associated with infected erythrocytes binding to receptors such as ICAM-1 expressed on the endothelial cells of the host microvasculature. Here, we use a static protein assay [3] to determine if naturally occurring human P. knowlesi infections can cause erythrocytes to bind to ICAM-1, VCAM-1 and CD36.